2012
DOI: 10.1152/ajpheart.00407.2012
|View full text |Cite
|
Sign up to set email alerts
|

Vascular insulin resistance related to endoplasmic reticulum stress in aortas from a rat model of chronic kidney disease

Abstract: Here we tested the hypothesis that vascular insulin signaling was impaired and related with endoplasmic reticulum (ER) stress in aortas from the reduced renal mass (RRM) model of CKD. The activity of insulin signaling and markers of ER were determined in aortas from rats with RRM and cultured human umbilical vein endothelial cells. Tyrosine phosphorylation of insulin receptor-␤ and insulin receptor substrate (IRS)-1 and phosphorylation of protein kinase B and endothelial nitric oxide synthase were all decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 55 publications
0
14
0
1
Order By: Relevance
“…In the past decade, the ER has been identified as an important regulator of metabolic processes,35 and Gargalovic et al were among the first to directly link ER stress to endothelial disturbances 36. Experimental studies in cultured endothelial cells have demonstrated that chemically induced ER stress causes endothelial dysfunction and insulin resistance 37, 38. Further, a number of studies in animal models have provided additional insights into the molecular mechanisms linking ER stress induction and endothelial dysfunction 39, 40.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, the ER has been identified as an important regulator of metabolic processes,35 and Gargalovic et al were among the first to directly link ER stress to endothelial disturbances 36. Experimental studies in cultured endothelial cells have demonstrated that chemically induced ER stress causes endothelial dysfunction and insulin resistance 37, 38. Further, a number of studies in animal models have provided additional insights into the molecular mechanisms linking ER stress induction and endothelial dysfunction 39, 40.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with in vitro data, ATX or ATX/Alo treatment did not change the serum ET‐1 levels. A recent study revealing the relationship between nondiabetic chronic kidney disease and vascular insulin resistance suggested the involvement of ER stress in the aorta (35). The potential for relatively low concentrations of uric acid to induce ER stress in rat glomerular mesangial cells displays many similarities to the findings of the present study (36).…”
Section: Discussionmentioning
confidence: 99%
“…This information suggests that ER stress may be one key pathway leading to metabolic disease states. Although ER stress has been demonstrated in the kidney [17] and aorta [18] in the context of CKD, whether In the present study, we tested the hypothesis that the inhibition of ER stress could alleviate lipolysis in white adipose tissue under the conditions of CKD. Our data showed that ER stress was activated and lipolysis was enhanced in visceral white adipose tissue in rats with reduced renal mass (RRM), a model of CKD.…”
Section: Introductionmentioning
confidence: 89%